Lifetime of Liquid Metal Wires for Stretchable Devices. Issue 4 (12th February 2021) - Dorsey, Kristen L.; Lazarus, Nathan
Abstract: As stretchable devices become well established for applications in soft robotics and wearable devices, the compliant conductors that make these applications possible must also be reliable and survive for the entire device lifetime. Liquid metals such as Galinstan are a potential solution as non‐toxic, stretchable, and low‐resistance conductors. Rigorous investigations of liquid metal lifetimes, however, are limited. This work presents the median lifetime of liquid metal‐filled silicone tubes under current density on the order of 1 kAcm −2, which is necessary for applications such as electromagnetic actuators. In these conductors, the median lifetime increases by a factor of over 4700 as current decreases from 2 to 1 kAcm −2 . By cooling the sample, median failure time increases from 112 s to 9.4 h, which suggests straightforward solutions to maximize liquid metal wire lifetime by increasing thermal conductivity or by duty cycling the applied current. Abstract : Liquid metals must withstand high current densities to meet applications in stretchable electromagnetic actuation, heating, and power transfer. After applying current, open circuit failures are visible in the wires. The lifetime ranges from a median of 112 s to over 100 h for current densities from 1–2 kAcm −2 .